Multiple Strategies for the Application of Medicinal Plant-Derived Bioactive Compounds in Controlling Microbial Biofilm and Virulence Properties - Mulugeta Mulat; Riza Jane S. Banicod; Nazia Tabassum; Aqib Javaid; Abirami Karthikeyan; Geum-Jae Jeong; Young-Mog Kim; Won-Kyo Jung; Fazlurrahman Khan (Antibiotics, 2025)
Biofilms are complex microbial communities encased within a self-produced extracellular matrix, which plays a critical role in chronic infections and antimicrobial resistance. These enhance pathogen survival and virulence by protecting against host immune defenses and conventional antimicrobial treatments, posing substantial challenges in clinical contexts such as device-associated infections and chronic wounds. Secondary metabolites derived from medicinal plants, such as alkaloids, tannins, flavonoids, phenolic acids, and essential oils, have gained attention as promising agents against biofilm formation, microbial virulence, and antibiotic resistance. These natural compounds not only limit microbial growth and biofilm development but also disrupt communication between bacteria, known as quorum sensing, which reduces their ability to cause disease. Through progress in nanotechnology, various nanocarriers such as lipid-based systems, polymeric nanoparticles, and metal nanoparticles have been developed to improve the solubility, stability, and cellular uptake of phytochemicals. In addition, the synergistic use of plant-based metabolites with conventional antibiotics or antifungal drugs has shown promise in tackling drug-resistant microorganisms and revitalizing existing drugs. This review comprehensively discusses the efficacy of pure secondary metabolites from medicinal plants, both as individuals and in nanoformulated forms or in combination with antimicrobial agents, as alternative strategies to control biofilm-forming pathogens. The molecular mechanisms underlying their antibiofilm and antivirulence activities are discussed in detail. Lastly, the current pitfalls, limitations, and emerging directions in translating these natural compounds into clinical applications are critically evaluated.